Asignación óptima de capital en base al perfil de riesgo de las instituciones de inversión colectiva: Una aplicación de las medidas de riesgo distorsionadas - Jaume Belles-Sampera; Miguel Santolino (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– Increasing attention is paid to risk management under the recent regulatory frameworks of the insurance and financial sectors. It is required by the regulator that institutions have a capital to face potential losses from their activity. This capital is usually assessed by means of risk measures. To take adequate decisions, it is essential that managers know how individual risk contribute to the aggregated capital requirement. Techniques of optimal capital allocation are developed to deal with it. This article applies optimal capital allocation criteria in the context of asset management. Our goal is to analyze the liquidity coefficients of Collective Investment Schemes (IIC) belonging to a Management Company of Collective Investment Schemes. In this new context, the risk undertaken by each IIC is assessed with alternative distortion risk measures. We develop a fictitious case where results suggest that the risk profile of institutions should be a key factor to determine liquidity coefficients in order to not penalize conservative strategies.
Keywords: G11; G23; G32; 330; capital allocation; distortion risk measures; risk profile; aggregated risk